2017
DOI: 10.1080/09712119.2017.1285771
|View full text |Cite
|
Sign up to set email alerts
|

First incidence of loose-shell syndrome disease in the giant tiger shrimp Penaeus monodon from the brackish water ponds in Bangladesh

Abstract: The recent incidence of loose-shell syndrome disease (LSSD) in grow-out shrimp ponds appears to be a major problem in Bangladesh. Therefore, the aims of our study were (i) to observe clinical signs of LSSD to confirm its incidence and (ii) to identify the probable causative agents for LSSD in shrimp. Sampling was conducted randomly from five LSSD-affected ponds and three non-affected ponds near Bakkhali River; ecological parameters were measured. A total of 180 healthy shrimps were used for this experiment, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The results of this study clearly showed that feeding with S. chartreusis remarkably improved growth response and feed utilization. These results are in parallel with [25] who Data are presented as the mean ± S:D: Data assigned with different superscripts in a column present a significant difference at P < 0:05. 5 Aquaculture Nutrition found that tiger shrimp (Penaeus monodon) fed diets supplemented with Streptomyces fradiae and Bacillus megaterium as probiotics has improved growth performance and feed efficiency.…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study clearly showed that feeding with S. chartreusis remarkably improved growth response and feed utilization. These results are in parallel with [25] who Data are presented as the mean ± S:D: Data assigned with different superscripts in a column present a significant difference at P < 0:05. 5 Aquaculture Nutrition found that tiger shrimp (Penaeus monodon) fed diets supplemented with Streptomyces fradiae and Bacillus megaterium as probiotics has improved growth performance and feed efficiency.…”
Section: Discussionsupporting
confidence: 79%
“…The IQ Plus™ WSSV kit requires the use of POCKIT™ device (GeneReach), a portable nucleic acid analyser equipped with a thermal controller and a fluorescent detector. The WOAH‐certified kits are being widely used by many researchers, worldwide 52–54 . However, it seems that the other diagnostic kits are not commonly used in scientific studies, except for the single‐tube WSSV detection kit (GeNei, India), which has been cited in a few research articles and has a detection limit of 10 viral particles per reaction, with detection times ranging from ~3.5 to 4 h 55–57 …”
Section: Molecular Diagnostic Methods For Shrimp Viral Diseasesmentioning
confidence: 99%
“…Bangladesh ranked 12th in the world in culturing shrimp (FAO 2018); the giant tiger shrimp Penaeus monodon was the top species (AftabUddin et al 2018). The global production of Penaeid shrimps has exceeded 4200 metric tonnes with a value of USD 4.8 billion in 2016 (GAA (Global Aquaculture Alliance) 2017).…”
Section: Introductionmentioning
confidence: 99%